Detection of Francisella tularensis and analysis of bacterial growth in ticks in Japan. (1st October 2016) - Suzuki, J.; Hashino, M.; Matsumoto, S.; Takano, A.; Kawabata, H.; Takada, N.; Andoh, M.; Oikawa, Y.; Kajita, H.; Uda, A.; Watanabe, K.; Shimizu, T.; et al.
Abstract: Francisella tularensis is distributed in the Northern hemisphere and it is the bacterial agent responsible for tularaemia, a zoonotic disease. We collected 4 527 samples of DNA from ticks in Japan, which were then analysed by real‐time PCR and nested PCR. Francisella DNA was detected by real‐time PCR in 2·15% (45/2 093) of Ixodes ovatus, 0·66% (14/2 107) of I. persulcatus, 8·22% (6/73) of I. monospinosus and 0·72% (1/138) of Haemaphysalis flava specimens. Finally, Francisella DNA was detected by nested PCR in 42 and five samples I. ovatus and I. persulcatus, respectively, which were positive according to real‐time PCR. Phylogenetic analysis showed that the sequence from I. ovatus and I. persulcatus were clustered with F. tularensis type B strains distributed in Eurasia. Microinjected live F. tularensis persisted in ticks, whereas heat‐killed F. tularensis decreased. Microinjected F. tularensis hlyD mutant decreased in ticks significantly compared to parent strain, thereby suggesting that HlyD in F. tularensis contributes to the adaptation or survive of bacterial infection in ticks. Significance and Impacts of the Study: Francisella tularensis has been detected in ticks, suggesting that it is a tick‐borne pathogen. However, F. tularensis has not been detected in ticks in Japan since 1991. In this study, we performed a large‐scale analysis of DNA isolated from ticks in Japan and detected F. tularensis by real‐time polymerase chain reaction (PCR) and nested PCR. We found that F. tularensis could survive in ticks based on an experimental tick‐infection model. We also identified a bacterial factor that contributes to survival in ticks. Our results suggest that ticks are candidate vectors that mediate F. tularensis infection in Japan.